Trait mindfulness and personality characteristics in a microdosing ADHD sample: a naturalistic prospective survey study - Haijen, Eline C. H. M.; Hurks, Petra P. M.; Kuypers, Kim P. C. (Frontiers in Psychiatry, 2023)
Background: Microdosing (MD), repeatedly taking psychedelics in small, non-hallucinogenic amounts, has been practiced by individuals to relieve attention deficit hyperactivity disorder (ADHD) symptoms. Generally, adults diagnosed with ADHD have lower levels of mindfulness and differ in personality structure from non-ADHD adults. How MD affects mindfulness and personality in adults with ADHD remains unexplored. Aim: This study aimed to investigate the effects of four weeks of MD on mindfulness and personality traits in adults diagnosed with ADHD and those experiencing severe ADHD symptoms. It was expected that mindfulness and the personality traits conscientiousness, extraversion, agreeableness, and openness would increase and neuroticism would decrease after four weeks of MD compared to baseline. It was explored if using conventional ADHD medication alongside MD and/or having comorbidities influenced MD-induced effects. Methods: An online prospective naturalistic design was used to measure participants before MD initiation and two and four weeks later. Validated self-report measures were used assessing mindfulness (15-item Five Facet Mindfulness Questionnaire) and personality traits (10-item version of the Big Five Inventory) at three time points. Results: The sample included n= 233, n= 66, and n= 44 participants at the three time points, respectively. Trait mindfulness, specifically description and non-judging of inner experience, was increased, and neuroticism was decreased after four weeks of MD compared to baseline. The remaining personality traits remained unchanged. Using conventional medication and/or having comorbid diagnoses did not change the MD-induced effects on mindfulness and personality traits after four weeks. Conclusions: MD induced changes in otherwise stable traits. Future placebo-controlled studies are warranted to confirm whether these changes occur in a controlled setting.